Corporate Social Responsibility: A Social And Spiritual Perspective - Fitriadi, Fitriadi; Alimuddin, Alimuddin; Mediaty, Mediaty (Jurnal Akuntansi Manado (JAIM), 2024)
This research comprehensively discusses social responsibility from social and spiritual perspectives. Using a systematic literature review, the research examines the role of social responsibility in social and spiritual aspects. This paper is the first to discuss CSR from two perspectives simultaneously. The research results show that the integration of social and spiritual values in business practices within companies can encourage greater social responsibility and contribute to community welfare, enhance the company's reputation, create a positive corporate culture, and build strong relationships with stakeholders. This research is expected to serve as literature for companies in conducting their business without neglecting social interests by using a spiritual approach in their management.